(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Impressions and questions regarding the teleperformance Esqueceram de Mim s/n (Home Alone, no number), which happened as part of the virtual event X Performance Show - Afroindigene: Body, Image, Violence and (Re)Presentation (11/30 to 12/02/2020). The piece was created by the AFFECTUS Dance Theater Collective of Federal University of Bahia (UFBA), also with the participation of former artists/researchers of UFBA, in different locations of Brazil. The poetic and performative writing deals with aspects of disability, invisibility and exclusion, searching to validate somatic sensitivities and ancestral memories, with an emphasis on difference and on singularities as modes of creating innovative and fundamental wisdoms in contemporary times.